Parenting Patterns of Sasak Parents in Sade Village Central Lombok Regency - Wahyuni Murniati; Farida Rohayani (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
This research aims to determine the parenting patterns implemented by parents in Sade Hamlet, Central Lombok. Sade Hamlet is a place known for its various unique qualities, one of which is the Nyesek Tradition. This tradition is also part of the parenting style implemented by parents in Sade Hamlet, so it is interesting to study in more depth. The research approach used is a qualitative approach with a postpositivism paradigm. Data collection methods were carried out using observation, interviews and literature reviews with primary data in the form of parents and traditional elders in Sade Hamlet and subject determination was carried out using purposive sampling techniques, namely parents in Sade Hamlet who had children aged 0-8 years. The results of the research show that parents in Sade Hamlet apply authoritarian, democratic and permissive parenting patterns with the majority having a permissive parenting style which has impacts such as a lack of politeness and respect for parents, children become individuals who always want to be obeyed, are selfish and often control. parent. Parenting patterns in Sade Hamlet are influenced by several factors such as community environment, culture, parenting patterns obtained from previous parents, parents' educational background; economic conditions.